2019
DOI: 10.3390/app9081680
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure of Coals by Mercury Intrusion, N2 Adsorption and NMR: A Comparative Study

Abstract: Coalbed methane (CBM) mainly adsorb in massive pores of coal. The accurate characterization of pores benefits CBM resource evaluation, exploration and exploitation. In this paper, mercury intrusion porosimetry (MIP) and low temperature nitrogen adsorption (N2GA) combined with low field nuclear magnetic resonance (NMR) experiments were conducted to analyze the advantages and differences among different experimental techniques in pore characterization. The results show that the total porosity has a tendency to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…It is 9 Geofluids noteworthy that moist forest peat swamp facies samples from YV-1 well, which are medium-rank coal with R o of 0.95%-1.1%, have poorer porosity (2.66%-4.22%) and TPA (3.23-5.98 m 2 /g) and slightly larger MPD (8.1-8.2 nm) and (16.2-26.2 nm) than the same coal facies samples from PQ-1 well. This result is consistent with former researchers, and they indicated that micropores proportion reach peak during 0.75%-1.25% R o stage, while the peak of macropores occurs during 2.0%-2.5% R o stage (Figure 9) [33][34][35][36][37][38].…”
Section: 2supporting
confidence: 93%
See 1 more Smart Citation
“…It is 9 Geofluids noteworthy that moist forest peat swamp facies samples from YV-1 well, which are medium-rank coal with R o of 0.95%-1.1%, have poorer porosity (2.66%-4.22%) and TPA (3.23-5.98 m 2 /g) and slightly larger MPD (8.1-8.2 nm) and (16.2-26.2 nm) than the same coal facies samples from PQ-1 well. This result is consistent with former researchers, and they indicated that micropores proportion reach peak during 0.75%-1.25% R o stage, while the peak of macropores occurs during 2.0%-2.5% R o stage (Figure 9) [33][34][35][36][37][38].…”
Section: 2supporting
confidence: 93%
“…Especially in Guizhou Province, where the coal reservoirs are multilayer thin coal seams [7]. In addition, previous studies have proved that coal rank is another controlling factor to reservoir properties (Figures 9 and 12) [33][34][35][36][37], and coal rank reflects tectonic evolution of coal reservoir. Generally, medium rank coal has much higher 12 Geofluids proportion of micropores and lower proportion of macropores than low and high rank coals.…”
Section: Applications Of Coal Facies In Cbm Industry For Guizhoumentioning
confidence: 99%
“…This technique expands the concept of the Langmuir adsorption isotherm by assuming perfect multilayer adsorption via the formation of monolayers [115]. The BET data are obtained by injecting N 2 gas at 77 K into a coal sample and provide information related to the type of pores in which adsorption occurs, the SSA of the material and the total pore volume [37,62,74,96,116,117]. The BET method is also used to calculate the SSA values of mesoporous solids in general [77,118].…”
Section: Bet Methodsmentioning
confidence: 99%
“…12−14 For further understanding the heterogeneous pore structure of coal, many scholars have carried out a lot of research by using the above methods. The experimental results of Zhu et al 15 showed that due to the compaction in the early stage and the thermogenic gas produced in the middle and late stages of coalification, the total porosity tends to decrease first and then increase. Xu et al, 16 through a series of pore-detection experiments, showed that adsorption pores (<100 nm) are more well developed for disturbed coal than for primary coal.…”
Section: Introductionmentioning
confidence: 99%